MUSEUM SONGKET PALEMBANG DENGAN PENDEKATAN ARSITEKTUR NEO-VERNAKULAR - Abdul Aziz Arrosyid; Samsudi Samsudi; Ummul Mustaqimah (ARSITEKTURA, 2016)
Traditional weaving as a national cultural heritage is being abandoned, including songket in Palembang city. Songket weaving craft has been abandoned due to the limited process of the making, expensive raw materials, and competitiveness, either other crafters or modern weaving. There are hundreds of Palembang songket motifs that have not been documented and collected well. Only 77 motifs which have been registered as intellectual property rights. The lack attention of this matter would give possibility for neighboring countries to claim it such an accident ever exist. Songket Museum is needed as conservation center, exhibition, research, and songket craft workshop. Neo-Vernacular Architecture approach is used to make museum architectural design which is in line the cultural values of Palembang in contemporary design. The design issue is how to apply the principles of Neo-Vernacular Architecture into Palembang Songket Museum design. The method is designing the museum by taking both the physical and non-physical elements of local culture. Beside, re-interpretation the shape and philosophycal value of local architecture and Palembang songket are apllied in a new composition of Neo-Vernacular Architecture. The result is a design of Palembang Songket Museum which applies Neo-Vernacular Architecture principles. Keywords: Architecture, Neo-Vernacular, Palembang Songket, Songket Museum.